Peran Hukum Pidana dalam Pencegahan Kekerasan Seksual terhadap Anak: Tinjauan terhadap Kebijakan dan Implementasi di Indonesia - Haryanto, Revita Fadya (UM Purwokerto Press, 2024)
Children are important assets for the nation and state, especially the next generation. Every child has the same human rights as humans in general. Children's rights have been neatly regulated in positive legislation in Indonesia in the form of protection from various crimes so that their rights are not violated, considering that there are so many cases of crimes experienced by children, especially criminal acts of sexual abuse. The law is required to be able to pay special attention to the interests of children, in this case it can overcome acts of sexual violence that are experienced by many Indonesian children. The Sexual Violence Law No. 12 of 2022 is an addition to the new government regulations that need to be studied more deeply with the aim of helping to fight sexual crimes. This research discusses a deeper study of the role of criminal law in acts of sexual violence against children using normative juridical research with an approach to theories, concepts, legal principles, and legislation. The role of Criminal Law in preventing sexual violence covers several aspects, including protection from government agencies, criminal responsibility, and ensuring law enforcement.